Teacher-Students Relationship and its Potential Impact on Mathematics Learning - Dahal, Niroj; Luitel, Bal Chandra; Pant, Binod Prasad (Mathematics Education Forum Chitwan, 2019)
This article portrays lived experiences, and is an exploration of pedagogical practices as learners, as teachers, as teacher educators and educational researcher focusing on the relationship between teachers and students shifting from traditional to transformative approach in teaching and learning. Based on lived experiences as students of mathematics from school level to university, and as teachers of mathematics in different institutions in different time, the aim of this article is to examine and explore deep settled behavioural practices and seek to change towards transformative/constructive approach of learning and teaching in terms of teacher-student relationship to maintain quality of instruction for future generation in Nepal. Subscribing interpretive, critical, and postmodern research paradigms to embrace multi-paradigmatic research design (Taylor, Taylor & Luitel, 2012), we used auto-ethnography as a fusion research methodology in this study. Further, the auto-ethnographic inquiry also helped us to examine the pedagogical, cultural and contextual learning from different perspectives as students, teachers, teacher educators and educational researchers thereby offering space for interpretation, transformation and envisionary. We landed with the ideas that students’ active participation in learning, social and cultural enactment and transformative pedagogy promote our practice to be more meaningful, and learner centered which, in turn, develops a cordial relationship. Our vision to develop the cordial relationship between teacher-students is focused a bit differently in this article.